Potential Antibacterial Efficacy of Bioactive Principles of Fruit Extracts of Acacia arabica Lam. Willd against Enterotoxigenic Escherichia coli - Roymon and M. Lalita, Deboshree Biswas*, V. Shanti, M.G. (Journal of Ecobiotechnology, 2011)
The present study revealed antibacterial activity of six different fruit extracts of Acacia arabica against ETEC Enterotoxigenic E.coli strains. Preliminary phytochemical analysis of plant extracts and quantitative estimation revealed presence of large amount of tannins. In addition the extract was found to be rich in cardiac glycosides. Antibacterial activity of plant extracts by well-diffusion and broth microdilution method revealed that fruit extract of Acacia arabica act as alternative therapeutic agent to cure diarrhea associated with ETEC more effectively.